Transcriptome Analysis Reveals Cr(VI) Adaptation Mechanisms in Klebsiella sp. Strain AqSCr - Lara, Paloma; Vega-Alvarado, Leticia; Sahonero-Canavesi, Diana X.; Koenen, Michel; Villanueva, Laura; Riveros-Mckay, Fernando; Morett, Enrique; Juárez, Katy (Frontiers in Microbiology, 2021)
Klebsiella sp. strain AqSCr, isolated from Cr(VI)-polluted groundwater, reduces Cr(VI) both aerobically and anaerobically and resists up 34 mM Cr(VI); this resistance is independent of the ChrA efflux transporter. In this study, we report the whole genome sequence and the transcriptional profile by RNA-Seq of strain AqSCr under Cr(VI)-adapted conditions and found 255 upregulated and 240 downregulated genes compared to controls without Cr(VI) supplementation. Genes differentially transcribed were mostly associated with oxidative stress response, DNA repair and replication, sulfur starvation response, envelope-osmotic stress response, fatty acid (FA) metabolism, ribosomal subunits, and energy metabolism. Among them, genes not previously associated with chromium resistance, for example, cybB, encoding a putative superoxide oxidase (SOO), gltA2, encoding an alternative citrate synthase, and des, encoding a FA desaturase, were upregulated. The sodA gene encoding a manganese superoxide dismutase was upregulated in the presence of Cr(VI), whereas sodB encoding an iron superoxide dismutase was downregulated. Cr(VI) resistance mechanisms in strain AqSCr seem to be orchestrated by the alternative sigma factors fecl, rpoE, and rpoS (all of them upregulated). Membrane lipid analysis of the Cr(IV)-adapted strain showed a lower proportion of unsaturated lipids with respect to the control, which we hypothesized could result from unsaturated lipid peroxidation followed by degradation, together with de novo synthesis mediated by the upregulated FA desaturase-encoding gene, des. This report helps to elucidate both Cr(VI) toxicity targets and global bacterial response to Cr(VI).